Multifunctional Biocomposite Membrane of Bacterial Cellulose/Chitosan Incorporated with Green Tea Leaf Extract as a Smart Colorimetric Sensor for Sustainable Packaging - Nguyen, Tuan Anh; Do , Thi Hanh; Ha, Thi Dung (Trends in Sciences, 2025)
This study presents the development of multifunctional biocomposite films based on bacterial cellulose (BC) and chitosan (CS), integrated with green tea extract (GTE) rich in epigallocatechin gallate (EGCG), aimed at active food preservation, pharmaceutical packaging, and environmental remediation. EGCG was extracted using ultrasound-assisted extraction and quantified via high-performance liquid chromatography (HPLC), yielding approximately 5.01 mg/g of dried tea leaves. Composite films incorporating 0.2 - 0.4% EGCG (w/v) were fabricated and evaluated. At an optimal concentration of 0.3% EGCG, the film exhibited superior tensile strength (43 MPa), elongation at break (13.5%), and toughness ( 11 MJ/m³). Thermal analysis showed an increased degradation onset temperature ( 300 °C) and higher residual mass ( 30%), confirming improved thermal stability. Functionally, the BC/CS/EGCG film demonstrated strong UV absorption ( 81% at 280 nm) and reduced UV transmittance (<10% across 230 - 300 nm). The film also showed pH-responsive colorimetric behavior, with a color difference (ΔE) rising from 3.5 to 30.2 between pH 3 and 11. Heavy metal adsorption tests revealed maximum capacities of 26.96 mg/g (Pb²⁺), 24.51 mg/g (Fe³⁺), and 23.75 mg/g (Cu²⁺), with a limit of detection (LOD) for Pb²⁺ as low as 0.70 µM. Antibacterial activity was confirmed against E. coli (18 mm) and S. aureus (24 mm) at 0.3% EGCG. Notably, tablets wrapped in BC/CS/EGCG films experienced only 3.7% mass loss after 14 days under 75% humidity, compared to 21% for those wrapped in pure BC. These results demonstrate the excellent mechanical, optical, antibacterial, adsorptive, and sensing properties of the EGCG-integrated BC/CS films. The films hold strong potential for application as smart, sustainable materials in food packaging, moisture-sensitive pharmaceutical protection, and real-time environmental sensing. HIGHLIGHTS Multifunctional biocomposite films based on bacterial cellulose/chitosan were developed by integrating green tea extract rich in EGCG. The optimized film (0.3% EGCG) showed enhanced mechanical strength (43 MPa), thermal stability (onset 300 °C), and UV shielding ( 81% absorbance at 280 nm). The films exhibited pH-responsive colorimetric behavior, with ΔE increasing from 3.5 to 30.2 between pH 3 and 11, enabling real-time environmental sensing. Heavy metal adsorption capacities reached 26.96 mg/g (Pb²⁺) and LOD for Pb²⁺ was as low as 0.70 µM, indicating excellent remediation potential. Antibacterial activity was significant against E. coli and S. aureus, and films effectively protected pharmaceutical tablets under high humidity. GRAPHICAL ABSTRACT